ANALISIS KEBIJAKAN PENDIDIKAN MENGENAI PENGEMBANGAN DAN PENINGKATAN PROFESI GURU - Widya Wati; Lisna Yuniastika; Ayu firafita Ningsih (JURNAL MAPPESONA, 2020)
Teachers play a very strategic role in the framework of carrying out the functions and realize the goals of national education. The role of teachers can hardly be replaced by others, let alone in a multicultural and multidimensional society. Therefore, guidance and professional development of teachers should always be a top priority. This study aims to analyze educational policies related to the development and improvement of the teaching profession. The research method used in this study is a qualitative method with the type of descriptive approach case study. The results of this study indicate that with the existence of an educational policy on the development and improvement of the teaching profession, the position of teachers increasingly shaded by legal sources and with the Professional Teacher Education, teachers become more knowledge and professionalism as a teacher.